2016
DOI: 10.17795/jjnpp-32325
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Evaluation and Antioxidant Activity of Essential Oil, and Aqueous and Organic Extracts of Artemisia dracunculus

Abstract: Background: The genus Artemisia has various medicinal effects. Artemisia dracunculus (tarragon) is one of the species that belongs to the genus Artemisia, cultivated in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…Overall, according to the three tests used in this study (ABTS radical scavenging activity, Reducing power and Phosphomolybdenum assay), the obtained antioxidant activity of the RaEO might be attributed to the presence of high percentages of mainly germacrene D (49.2 ± 1.1%), methyl eugenol (8.3 ± 0.28%), (E)-β-ionone (6.2 ± 0.18%) and β-caryophyllene (5.7 ± 0.17%) (Table 1 ). Similarly to our results, some works reported that several essential oils having low phenolic compounds amounts also exhibits interesting antioxidant capacity [ 43 , 44 ]. However, it’s difficult to correlate the antioxidant activity of a total essential oil to one or few active compounds.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, according to the three tests used in this study (ABTS radical scavenging activity, Reducing power and Phosphomolybdenum assay), the obtained antioxidant activity of the RaEO might be attributed to the presence of high percentages of mainly germacrene D (49.2 ± 1.1%), methyl eugenol (8.3 ± 0.28%), (E)-β-ionone (6.2 ± 0.18%) and β-caryophyllene (5.7 ± 0.17%) (Table 1 ). Similarly to our results, some works reported that several essential oils having low phenolic compounds amounts also exhibits interesting antioxidant capacity [ 43 , 44 ]. However, it’s difficult to correlate the antioxidant activity of a total essential oil to one or few active compounds.…”
Section: Discussionsupporting
confidence: 91%
“…Both assays identified the EO and estragole (2) as weaker antioxidants than BHT and vitamin E, and compound 2 was less active than the EO. 20 In addition to the beneficial antioxidant properties, there are data, although contradictory, that allylpolyalkoxybenzenes exhibit genotoxic effects. Estragole (2), methyl eugenol (3), safrole (4), myristicin (5), apiol (7), and dillapiol (8) were reported to form DNA adducts in HepG2 human hepatoma cells, which may cause mutations, eventually leading to carcinogenesis.…”
mentioning
confidence: 99%
“…These results are in agreement with the antioxidant activity of tarragon reported previously. 7,8,32 Tarragon essential oil collected from Tajikistan demonstrated only very weak antibacterial activity against both Grampositive (Staphylococcus aureus) and Gram-negative (Pseudomonas aeruginosa and Escherichia coli) bacteria.…”
Section: Resultsmentioning
confidence: 99%